Efforts of Al-Qur'an Hadith Teachers in Overcoming Difficulties in Reading the Qur'an for Students - Muallief Umar; Dewi Fina Fitriyani; Zainur Arifin; Mustajib Mustajib; Devi Mariatul Qiptiah (STAI Miftahul Ula Nganjuk, 2024)
This study investigates the efforts of Al-Qur'an Hadith teachers in addressing the difficulties faced by seventh-grade students in reading the Qur'an at Madrasah Tsanawiyah Masyariqul Anwar, Ngronggot. The research employs a qualitative approach with a case study design, gathering data through observations, interviews, and document analysis from teachers and students. The findings reveal that students struggle with various aspects of Qur'anic reading, including recognizing the transformation of connected Hijaiyah letters, proper pronunciation with correct makhraj, distinguishing between long and short vowels, and applying Tajweed rules. To overcome these challenges, teachers are encouraged to adopt engaging teaching methods, create a conducive learning environment, and emphasize the significance of the Qur'an in a Muslim's life. These strategies are crucial in improving students' Qur'anic literacy and fostering a deeper connection with the holy text.